Status Probiotik Lactobacillus plantarum IIa-2C12 Sosis Fermentasi di Saluran Pencernaan Tikus Rattus novergicus - Kautsar, R.; Arief, I. I.; Suryati, T. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
The aim of the research was to evaluate the effect of fermented sausages using probiotic bacterial L. plantarum IIA-2C12 to the gastrointestinal tract of rats. The research was conducted from March to June 2014. Research was conducted at Breeding and Genetics Laboratory, Faculty of Animal Husbandry Laboratory Large Ruminants and UPH Faculty of Veterinary Medicine, Bogor Agricultural University. This study was divided into two stages, 1) subculturing (fermented sausage and beef satay) starter culture, the manufacture of casein, beef satay and sausage fermentation and, 2) in vivo evaluation. Rats were divided into three groups: casein (P1), fermented sausages (P2) and beef satay (P3). This research used a pattern completely randomized design with three treatments type of feed is feed casein, fermented sausage and beef satay. The results showed that based on the amount of lactic acid bacteria, fermented sausage produced met the criteria as a probiotic food. Fermented sausages could increased the population of LAB on the 20th day mucose (T2). Treatment of feed had no significant effect (P> 0.05) in the number of E. coli in the rat liver, but on the 10th day termination (T1), the rats P1 showed the number of BAL were significantly (P <0.05) higher than P2. Fermented sausage increased the population of LAB, decreased E. coli population in mucosa until 20th day in mucosa.